Kemampuan Penalaran Deduktif Matematis Siswa Melalui Modeling The Way - Hr, Bq. Malikah (Media Pendidikan Matematika, 2020)
The purposes of this research were to determine: (1) is there a significant difference between the mathematical deductive reasoning abilities of students before and after learning of modeling the way (2) whether learning of modeling the way can improve the mathematical deductive reasoning abilities of students. The research was a quasi-experimental research, with one group pretest-posttest design. The location of this research was in MA NW Kabar, Sakra Sub-District, East Lombok Regency. The sample of this research were students of class XI MA NW Kabar. Instrument of this research was the mathematical deductive reasoning abilities test. The data of this research was analyzed using descriptive statistics with paired sampel t-test. The results of the research indicated as follows: (1) There is a significant difference between the mathematical deductive reasoning abilities of students before and after learning of modeling the way; (2) Based on the average and percentage of the mathematical deductive reasoning abilities test of students, the average of pretest is 49.48 with 40% of the students have the mathematical deductive reasoning abilities with good category, the average of posttest is 68.09 with 80% of the students have the mathematical deductive reasoning abilities with good category, it shows that the learning of modeling the way can improve the mathematical deductive reasoning abilities of students.